Flexural and adhesive strength of 5Y-PSZ translucent zirconia after irradiation with Er:YAG laser - Basso, Diana Ghiggi; Freitas, Patrícia Moreira de; Saraiva, Leonardo; Benetti, Paula (Brazilian Dental Science, 2026)
Objective: To evaluate the effect of Er:YAG laser irradiation on the adhesive and fracture strength of 5 mol% yttria partially stabilized polycrystalline zirconia (5Y-PSZ). Material and Methods: Disc-shaped zirconia specimens (CPs) were divided into three groups (n=30): no treatment (Ctrl), airborne-particle abrasion with 50-µm aluminum oxide (Abr), and Er:YAG laser irradiation (Las). Composite resin cylinders (2 mm diameter × 5 mm height) were adhesively cemented to the CPs (n = 10) and were tested for microshear bond strength (µSBS). Fracture surfaces were examined by optical and scanning electron microscopy following fractographic principles, and failure modes were classified as adhesive, cohesive in resin, or mixed. Biaxial flexural strength (σf) was assessed using a piston-on-three-balls test (n=30), with the treated surface subjected to tensile stresses. The Weibull modulus (m) and characteristic strength (σ0 ) were calculated. Data were analyzed by ANOVA and Tukey tests (5%) (α = 0.05). Results: Laser-treated group showed µSBS values similar to both airborne-particle-abraded and control groups (p